Determination of Campus Promotion Policy Strategy Applied The Profile Matching Method - Indah Purnama Sari; Fatma Sari Hutagalung; Budi Kurniawan Hutasuhut (Journal of Computer Science, Information Technology and Telecommunication Engineering, 2020)
Decision support system, an application that is used to facilitate members of the university promotion team to determine the policy of the university's promotion strategy. This author discusses the decision support system for determining the university's promotional strategy policy with the profile matching method. The purpose of this paper is to make a decision support system application with a new method. The application used is matlab 7.10 which is used to test based on the results of weighting and calculation. The decision support system application that is produced is as expected in the weighting stage, both in testing, although there are still deficiencies in several respects. The adoption of a decision support system for determining the campus promotion strategy policy with the profile matching method can facilitate university promotion team members in making a wise decision. The method used in the implementation of this decision support system is the determination of the university promotion strategy policy with the profile matching method